Hydroxyethyl cellulose-aramid fiber / MXene nanometer friction positive electrode material and preparation method thereof

By using hydroxyethyl cellulose-aramid/MXene nano-friction positive electrode material, a composite film is prepared by vacuum suction filtration and coated with hydroxyethyl cellulose to form a sandwich structure material, the shortcomings of traditional materials in mechanical strength, friction performance and charge maintenance are solved, and efficient charge transfer and stable friction power generation effects are achieved.

CN119708589AActive Publication Date: 2025-03-28SHAANXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411928953.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

Traditional friction nanopower generation materials have shortcomings in mechanical strength, friction properties and charge retention, which limits their application effect in TENG.

Method used

Aramid/MXene composite film was prepared by vacuum suction filtration using hydroxyethyl cellulose-aramid/MXene nano-friction positive electrode material, and a sandwich structure was formed using hydroxyethyl cellulose as the shell layer.

Benefits of technology

It significantly improves the charge transfer efficiency, stability, mechanical properties and conductivity of the material, improves the friction power generation capacity and output voltage, and ensures long-term stability and high responsiveness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708589A_ABST
    Figure CN119708589A_ABST
Patent Text Reader

Abstract

The invention relates to the field of friction nanometer power generation, micro-nano energy collection and membrane material manufacturing, in particular to a hydroxyethyl cellulose-aramid fiber / MXene nanometer friction positive electrode material and a preparation method thereof.The positive electrode material is of a sandwich structure, a composite thin film formed by aramid nanofiber (ANF) and MXene through vacuum filtration is adopted as an inner layer, and an outer layer is adopted as an outer layer; the high strength and high modulus of aramid fiber and the high conductivity of MXene are combined. The hydroxyethyl cellulose on the outer layer is a protective layer, so that the structural strength of the material is enhanced, MXene is protected from being oxidized, and the stability and durability of the material are improved; rich hydroxyl functional groups on the surface of the contact friction layer are beneficial to easy transfer of charges, generation of friction voltage and providing of good electrostatic coupling induction and friction power generation capabilities, so that a new idea is provided for development of a friction nano power generation technology; and a more efficient and environment-friendly solution is provided for application in the fields of flexible wearing, self-powered equipment, micro-nano energy collection and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of friction nano power generation, micro-nano energy collection and membrane material manufacturing, and specifically to a hydroxyethyl cellulose-aramid / MXene nano friction positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of wearable devices, the Internet of Things, and portable electronic products, traditional battery power supply methods can no longer meet the requirements of these devices for portability, battery life, and environmental friendliness. As an emerging energy harvesting technology, the friction nanogenerator (TENG) is a micro-nano energy supply system device that converts tiny mechanical energy into electrical energy using friction electrification and electrostatic coupling effects. It has the outstanding advantages of high efficiency, sustainability, and environmental protection. The core of TENG lies in the selection and design of its positive and negative friction materials. These materials must have excellent charge retention ability, good mechanical properties, and environmental stability to ensure efficient energy conversion and long-term operational reliability.

[0003] Para-aramid fiber is considered as an ideal triboelectric material due to its orderly arrangement of amide bonds and the interaction between hydrogen bonds and π-π bonds in molecular chains; it has high strength, high modulus, good thermal stability and chemical stability. However, pure aramid fiber has low surface polarity, smooth surface, resulting in weak friction contact with other materials, and lack of conductive pathways on the surface. Therefore, in applications, it often faces problems such as low surface binding energy, low charge density, and poor charge transfer efficiency and stability, which limits its actual application effect in TENG.

[0004] On the other hand, as a new type of two-dimensional material, MXene has shown great potential in the field of energy storage and conversion; its unique layered structure composed of alternating metal atomic layers and carbon / nitrogen atomic layers and excellent conductivity enable it to provide efficient charge transfer during the process of electrical energy storage and conversion. MXene can improve the charge transfer efficiency of friction materials, but its surface activity is high, it is easy to agglomerate, and its structural stability needs to be improved during long-term friction.

[0005] Hydroxyethyl cellulose (HEC) is a water-soluble polymer containing polar groups such as hydroxyl (-OH) and ethoxy (-OCH2CH2). These polar groups make HEC molecules have strong hydrophilicity and polarity, good film-forming properties, lubricity and protection, and good charge transfer ability. In the preparation of triboelectric materials, HEC can be used as an effective coating material, which can not only enhance the mechanical strength of the composite material, but also improve its surface properties and enhance the charge retention capacity. Summary of the invention

[0006] In view of the problems that traditional materials are insufficient in mechanical strength, friction performance and charge retention, the present invention provides a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material and a preparation method thereof.

[0007] The present invention is achieved through the following technical solutions: A hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material, which has a sandwich structure, an inner layer of which is an aramid / MXene vacuum-filtered composite film, and an outer shell layer of which is a hydroxyethyl cellulose protective layer.

[0008] A method for preparing a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material comprises the following steps: Step 1, preparing a hydroxyethyl cellulose dispersion, an aramid nanofiber dispersion and a MXene dispersion; Step 2, after the aramid nanofiber dispersion and the MXene dispersion are evenly mixed, an ANF / MXene composite membrane is prepared by vacuum filtration and a first drying treatment; Step 3, immersing the ANF / MXene composite film in a hydroxyethyl cellulose dispersion, and then undergoing a second drying treatment to obtain an ANF / MXene-HEC triboelectric positive electrode material with a sandwich structure.

[0009] In step 1, the preparation method of the hydroxyethyl cellulose dispersion is as follows: dissolving 3-4 g of hydroxyethyl cellulose powder in 100-150 mL of deionized water at 45-55° C. for 30-40 min to obtain a hydroxyethyl cellulose dispersion; wherein the viscosity of the hydroxyethyl cellulose is 2600-3300 mPa.s.

[0010] In step 1, the aramid nanofiber mixed dispersion is prepared as follows: first, an alkaline solution, para-aramid fibers and dimethyl sulfoxide are stirred and mixed to obtain a dispersion A; wherein the mass ratio of the para-aramid fibers to the dimethyl sulfoxide is 2-3:200-300, the solute of the alkaline solution is potassium hydroxide, the concentration of the solute in the alkaline solution is 0.3-0.6 g / mL, and the ratio of the alkaline solution to the para-aramid fibers is 1-2 mL:2-3 g; Dispersion A is evenly dispersed in deionized water, and then filtered to obtain para-aramid nanofiber dispersion B; wherein the volume ratio of water to dispersion A is 1000-1500:50-100, and the concentration of the para-aramid nanofiber dispersion is 1%-1.5%.

[0011] Preferably, in step 1, the MXene aqueous dispersion is a nanosheet MXene aqueous dispersion prepared by an acid etching method, and the concentration of the MXene dispersion is 20 to 25 mg / mL.

[0012] Preferably, in step 2, the solution ratio of the aramid nanofiber dispersion and the MXene dispersion is 80-100 mL: 3-5 mL, and the mixture is stirred at 25-35° C. for 15-20 min to be uniformly mixed.

[0013] Preferably, in step 2, during vacuum filtration, the pressure is 0.08-0.10 MPa, the time is 3-4 h, and the filtration membrane is a mixed fiber membrane or a polytetrafluoroethylene membrane; During the first drying process, the temperature is 95~105℃ and the drying time is 12~15min.

[0014] Preferably, in step 3, during the immersion, the concentration of the hydroxyethyl cellulose dispersion is 0.02 to 0.04 g / mL, and the immersion time is 3 to 5 min.

[0015] Preferably, in step 3, during the second drying process, the temperature is 60-70° C. and the time is 6-8 hours.

[0016] A friction nano power generation device comprising hydroxyethyl cellulose-aramid / MXene nano friction positive electrode material.

[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention proposes a method for preparing a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material, in which aramid nanofibers and MXene are composited into a film through vacuum filtration, and hydroxyethyl cellulose is used for coating to form a sandwich structure, which combines the high strength and high modulus of aramid with the high conductivity of MXene and the outer HEC protective layer, thereby achieving a comprehensive improvement in charge transfer efficiency, stability, mechanical properties and conductivity. HEC not only provides the structural strength of the material as a protective layer, but also optimizes the accumulation and transfer of charges through its polar groups, significantly enhancing the friction power generation capability. At the same time, the synergistic effect of aramid and MXene enables the material to generate a higher output voltage during friction power generation, and exhibits good long-term stability and high responsiveness under various environmental conditions, providing a more efficient and stable solution for applications in the fields of micro-nano energy collection and self-powered equipment.

[0018] A sandwich structure is adopted, in which the inner layer is a dense layered film formed by vacuum filtration of a dispersion of aramid nanofibers (ANF) and MXene uniformly mixed at a pressure of 0.1MPa, and the outer layer is coated with a protective layer of hydroxyethyl cellulose (HEC). Aramid fibers provide high strength and high modulus, and the conductivity of MXene enhances the charge transfer capability. The outer layer of HEC not only protects the inner layer of MXene from oxidation, but also enhances the overall structural strength, providing better mechanical stability and durability. In addition, the flexibility and stretchability of the HEC layer ensure that the material can still maintain excellent friction properties in a dynamic environment, improving the long-term reliability and stability of the entire power generation device.

[0019] HEC is an outer protective film, and its surface is rich in hydroxyl functional groups (-OH). These polar groups enhance the material's charge accumulation ability and transfer efficiency. During the friction process, the hydroxyl groups on the HEC surface can effectively attract and fix charges. At the same time, the good lubricity of HEC reduces the charge loss between the friction surfaces. The surface polar groups also promote electrostatic coupling induction and increase the generation of friction voltage. HEC not only acts as a protective layer in triboelectric power generation, but also as an efficient charge transfer channel, enhancing the speed and stability of charge transfer.

[0020] The composite of aramid nanofiber (ANF) and MXene produces a synergistic effect and improves the overall performance of the material. The high strength and high modulus of aramid ensure the stability of the material during friction, while the highly conductive nanosheets of MXene form a conductive network inside the film, promoting the rapid conduction of charges. The layered structure of MXene not only provides a large number of ion conductive channels, but also during the friction process, MXene can provide efficient charge accumulation and transfer, significantly improving the output of triboelectric current. After the aramid fiber is composited with MXene, a tightly interwoven structure is formed, which enables the charge to be quickly transferred between the fiber and MXene, thereby significantly improving the charge storage capacity and triboelectric voltage output.

[0021] The composite of aramid nanofiber (ANF) and MXene produces a synergistic effect, significantly improving the friction output performance and mechanical strength of the material. The high strength and high modulus of aramid ensure the stability of the material during friction, while the high conductivity and layered structure of MXene provide a large number of ion conduction channels, forming a conductive network, effectively promoting the rapid conduction of charges, improving the efficiency of charge accumulation and transfer, and significantly enhancing the output of friction voltage. The tightly interwoven structure formed by the composite of aramid fiber and MXene, the connection of hydrogen bonds and intermolecular forces, enhances the mechanical strength and flexibility of the composite film.

[0022] As an outer protective film, HEC enhances the charge retention capacity of the material through hydrogen bonds and polar groups on its surface. When the materials come into contact and separate during friction, the surface of HEC not only supports the stable accumulation of charge, but also improves the electrostatic coupling induction ability by optimizing the surface friction performance, which helps to generate friction voltage more efficiently. Due to the coating of the HEC layer, the inner aramid / MXene composite film is protected, avoiding surface damage during long-term friction, ensuring the long-term stability and high response speed of the material. This improved stability ensures that the friction nanogenerator can continuously and stably output high voltage under various extreme working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a structural diagram of a hydroxyethyl cellulose-aramid / MXene nano-friction cathode material of the present invention; Figure 2 This is a SEM cross-sectional view of a hydroxyethyl cellulose-aramid / MXene nano-friction cathode material of the present invention; Figure 3 This is a flow chart of a hydroxyethyl cellulose-aramid / MXene nano-friction cathode material of the present invention; Figure 4 This is the friction voltage of the hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material prepared in Example 1 of the present invention.

[0024] Figure 5 This is the friction voltage of the hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material prepared in Example 2 of the present invention.

[0025] Figure 6 This is the friction voltage of the hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material prepared in Example 3 of the present invention.

[0026] Figure 7 The friction voltage of the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material prepared in Example 4 of the present invention; Figure 8 This is the friction voltage of the hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material prepared in Example 5 of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific embodiments, which are intended to explain the present invention rather than to limit it.

[0028] The present invention discloses a hydroxyethyl cellulose-aramid / MXene nano friction positive electrode material, referring to Figure 1The cathode material has a sandwich structure, with the inner layer being a composite film of aramid / MXene vacuum filtration and the outer shell being a hydroxyethyl cellulose protective layer. Figure 2 This is the SEM cross-sectional image of the aramid / MXene friction power generation positive electrode material. It can be clearly seen that the upper and lower thicker layers of hydroxyethyl cellulose membrane wrap the aramid / MXene vacuum filtered composite film in the middle, further verifying the sandwich structure.

[0029] Hydroxyethyl cellulose (HEC) is preferred as the contact friction layer because of its advantages: (1) Excellent film-forming property and processability: Hydroxyethyl cellulose has good film-forming property and solubility, and can be evenly coated on the surface of the composite material to form a continuous and smooth protective film. At the same time, the preparation process of HEC dispersion is simple, and the cost is low and the source is wide, which is convenient for large-scale processing, production and application; (2) Outstanding surface friction performance: Hydroxyethyl cellulose (HEC) is composed of a cellulose main chain and a hydroxyethyl side chain structure. It is a water-soluble polymer compound prepared by etherification reaction of cellulose and ethylene oxide (or chloroethanol). The surface is rich in hydroxyl groups, which help attract charge transfer in electrostatic coupling induction and have the inherent advantage of preparing high friction voltage positive electrode materials; (3) Biocompatibility and environmental protection: HEC is a renewable and environmentally friendly material with good biocompatibility and non-toxicity. It is widely used in medical and cosmetic fields. As a friction nano-power generation material, it has great advantages in the field of flexible wearables. (4) Flexibility and stretchability: As a flexible polymer, HEC film can give triboelectric nanomaterials good flexibility and certain stretchability, making them suitable for flexible electronic devices and wearable devices. Compared with traditional rigid materials, after HEC is combined with aramid / MXene composite film, the material can still maintain good electrical properties when bent or stretched, improving its reliability in dynamic environments.

[0030] The advantages of the inner film material of the composite vacuum filtration of aramid nanofibers and MXene nanosheets are (1) outstanding mechanical properties: aramid nanofibers have a linear rigid straight chain configuration due to the macromolecular chain composed of benzene rings and amide groups, which is not easy to deform when the fiber is stressed, and has the characteristics of high strength and high modulus. MXene and HEC are combined to form a composite film, which improves the overall mechanical properties and friction properties of the material through stress transfer; (2) high conductivity: the free electron transmission of metal atoms in the MXene layer, the formation of an electronic conjugated system, the ion conductive channel of the interlayer gap, and the excellent physical and chemical properties make it have good conductivity; the composite with aramid nanofibers forms a tightly interwoven layered structure, which can store and retain charges well. (3) Excellent temperature resistance and stability: aramid nanofibers have the characteristics of high temperature resistance, corrosion resistance, and wear resistance. They maintain stable triboelectric performance in a wide temperature range and harsh chemical environment, which is conducive to extending the service life of triboelectric nanoelectric materials. (4) Good flexibility and stretchability: The layered structure of MXene and aramid nanofibers are interwoven to form a composite membrane with excellent flexibility and stretchability, which is conducive to the wide application of the material in the fields of flexibility, wearable, and micro-nano energy harvesting.

[0031] The present invention also discloses a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material, referring to Figure 3 , including the following steps: Step 1, dissolving 3-4 g of hydroxyethyl cellulose powder in 100-150 mL of deionized water at 45-55° C. for 30-40 min to obtain a hydroxyethyl cellulose dispersion with a concentration of 0.02-0.04 g / mL; The alkaline solution, para-aramid fiber and dimethyl sulfoxide are stirred and mixed to obtain a dispersion A; wherein the mass ratio of the para-aramid fiber to the dimethyl sulfoxide is 2-3:200-300, the solute of the alkaline solution is potassium hydroxide, the concentration of the solute in the alkaline solution is 0.3-0.6 g / mL, and the ratio of the alkaline solution to the para-aramid fiber is 1-2 mL:2-3 g; Dispersion A is evenly dispersed in deionized water, and then filtered to obtain para-aramid nanofiber dispersion B; wherein the volume ratio of water to dispersion A is 1000-1500:50-100, and the concentration of the para-aramid nanofiber dispersion is 1%-1.5%.

[0032] Step 2, 80-100 mL of aramid nanofiber dispersion with a concentration of 1%-1.5% and 3-5 mL of MXene dispersion with a concentration of 20-25 mg / mL are stirred at 25-35° C. for 15-20 min to mix evenly, and then vacuum filtered at a pressure of 0.08-0.10 MPa for 3-4 h, and then dried at 95-105° C. for 12-15 min to prepare an ANF / MXene composite film; Step 3, immersing the ANF / MXene composite film in a hydroxyethyl cellulose dispersion for 3 to 5 minutes, drying it at 60 to 70°C for 6 to 8 hours, and finally obtaining an ANF / MXene-HEC triboelectric positive electrode material with a sandwich structure.

[0033] Example 1 Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 150 mL of deionized water at 55° C. for 30 min to obtain a 0.02 g / mL hydroxyethyl cellulose dispersion; Step 2, 100 mL of 1% aramid nanofiber dispersion and 3 mL of 25 mg / mL MXene dispersion were stirred at 25 ° C for 20 min to mix evenly, and then vacuum filtered at a pressure of 0.08 MPa for 3 h, and then dried at 105 ° C for 15 min to prepare an ANF / MXene composite film; Step 3: The ANF / MXene composite film is immersed in a hydroxyethyl cellulose dispersion for 3 minutes, and dried at 60°C for 6 hours to finally obtain a sandwich-structured ANF / MXene-HEC triboelectric positive electrode material.

[0034] In this embodiment, a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material has a hydroxyethyl cellulose concentration of 0.2 g / ml, a MXene content of 75 mg, a composite film thickness of 0.0049 mm, a tensile strength of 10.89 MPa, and a friction voltage of 640 V.

[0035] Example 2 Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 150 mL of deionized water at 55° C. for 30 min to obtain a 0.02 g / mL hydroxyethyl cellulose dispersion; Step 2, 100 mL of aramid nanofiber dispersion with a concentration of 1.5% and 4 mL of MXene dispersion with a concentration of 25 mg / mL were stirred at 25° C. for 20 min to mix evenly, and then vacuum filtered at a pressure of 0.08 MPa for 3 h, and then dried at 105° C. for 15 min to prepare an ANF / MXene composite film; Step 3: The ANF / MXene composite film is immersed in a hydroxyethyl cellulose dispersion for 3 minutes, and dried at 60°C for 6 hours to finally obtain a sandwich-structured ANF / MXene-HEC triboelectric positive electrode material.

[0036] In this embodiment, a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material has a hydroxyethyl cellulose concentration of 0.2 g / ml, a MXene content of 100 mg, a composite film thickness of 0.0052 mm, a tensile strength of 11.23 MPa, and a friction voltage of 680 V.

[0037] Example 3 Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 100 mL of deionized water at 55° C. for 35 min to obtain a hydroxyethyl cellulose dispersion with a concentration of 0.03 g / mL; Step 2, 100 mL of aramid nanofiber dispersion with a concentration of 1.5% and 3 mL of MXene dispersion with a concentration of 25 mg / mL were stirred at 25° C. for 20 min to mix evenly, and then vacuum filtered at a pressure of 0.08 MPa for 4 h, and then dried at 105° C. for 15 min to prepare an ANF / MXene composite film; Step 3: The ANF / MXene composite film is immersed in a hydroxyethyl cellulose dispersion for 3 minutes, and dried at 60°C for 7 hours to finally obtain a sandwich-structured ANF / MXene-HEC triboelectric positive electrode material.

[0038] In this embodiment, a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material has a hydroxyethyl cellulose concentration of 0.3 g / ml, a MXene content of 75 mg, a composite film thickness of 0.0065 mm, a tensile strength of 13.89 MPa, and a friction voltage of 732 V.

[0039] Example 4 Step 1, dissolving 3 g of hydroxyethyl cellulose powder in 100 mL of deionized water at 55° C. for 35 min to obtain a hydroxyethyl cellulose dispersion with a concentration of 0.03 g / mL; Step 2, 100 mL of aramid nanofiber dispersion with a concentration of 1.5% and 5 mL of MXene dispersion with a concentration of 25 mg / mL were stirred at 25° C. for 20 min to mix evenly, and then vacuum filtered at a pressure of 0.08 MPa for 4 h, and then dried at 105° C. for 15 min to prepare an ANF / MXene composite film; Step 3: The ANF / MXene composite film is immersed in a hydroxyethyl cellulose dispersion for 3 minutes, and dried at 60°C for 7 hours to finally obtain a sandwich-structured ANF / MXene-HEC triboelectric positive electrode material.

[0040] In this embodiment, a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material has a hydroxyethyl cellulose concentration of 0.3 g / ml, a MXene content of 125 mg, a composite film thickness of 0.0081 mm, a tensile strength of 14.56 MPa, and a friction voltage of 860 V.

[0041] Example 5 Step 1, dissolving 4 g of hydroxyethyl cellulose powder in 100 mL of deionized water at 55° C. for 40 min to obtain a hydroxyethyl cellulose dispersion with a concentration of 0.04 g / mL; Step 2, 100 mL of aramid nanofiber dispersion with a concentration of 1.5% and 5 mL of MXene dispersion with a concentration of 25 mg / mL were stirred at 25° C. for 20 min to mix evenly, and then vacuum filtered at a pressure of 0.08 MPa for 4 h, and then dried at 105° C. for 15 min to prepare an ANF / MXene composite film; Step 3: The ANF / MXene composite film is immersed in a hydroxyethyl cellulose dispersion for 3 minutes, and dried at 60°C for 8 hours to finally obtain a sandwich-structured ANF / MXene-HEC triboelectric positive electrode material.

[0042] In this embodiment, a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material has a hydroxyethyl cellulose concentration of 0.4 g / ml, a MXene content of 125 mg, a composite film thickness of 0.0096 mm, a tensile strength of 14.32 MPa, and a friction voltage of 1012 V.

[0043] Table 1 Technical parameters of high friction voltage sensing materials obtained in Examples 1 to 5

[0044] In the friction voltage test, the hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material was first cut into 5*5cm square pieces, and then copper foil tape and wires were attached to the back of the material in a grid-like structure to prepare the positive electrode device of the friction nanogenerator. In the same way, the negative electrode device of the friction nanogenerator was prepared using polytetrafluoroethylene film. The positive and negative electrode materials were connected to an oscilloscope, and a linear motor was used to give a uniform and stable impact force to make the positive and negative electrodes contact and separate, causing charge transfer and generating friction voltage.

[0045] Table 1 shows the technical parameters of a hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material prepared in Examples 1 to 5. It can be seen that the friction power generation positive electrode material prepared by the process provided by the present invention benefits from the use of hydroxyethyl cellulose film as the contact friction layer. Hydroxyethyl cellulose has good charge transfer ability, is conducive to generating friction voltage, and provides good electrostatic coupling induction and friction power generation capabilities. The higher the concentration of hydroxyethyl cellulose, the thicker the outer shell film, and the higher the friction output voltage of the material.

[0046] The introduction of aramid nanofibers enhances its toughness and strength, and the mechanical strength is in the range of 10-15MPa. As the concentration of hydroxyethyl cellulose increases, the HEC-PVDF-HEC film becomes thicker and thicker, and its mechanical strength increases. The friction voltage is greatly affected by the thickness of the hydroxyethyl film. The thicker the positive electrode material, the stronger the electrostatic coupling charge transfer ability, the more electrons are lost, the greater the potential difference between the positive and negative electrodes, and the greater the friction voltage. Similarly, the wide-bandgap charge retention phase PVDF film effectively improves the accumulation and transmission efficiency of charges, and also increases the friction voltage output by the material. This structural design not only enhances the overall performance of the material, but also improves the output stability and sensitivity of the nano friction generator.

[0047] Figures 3 to 7 The friction output voltage of the hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material prepared in Examples 1 to 5 was obtained by using a polytetrafluoroethylene film as the negative electrode to prepare a 5*5 cm square friction power generation device. Under the same frequency and external force, different friction output voltages were generated due to the different concentrations of hydroxyethyl cellulose and aramid / MXene composite film.

[0048] The above description is only a preferred embodiment of the present invention and is not intended to impose any limitation on the technical solution of the present invention. Those skilled in the art should understand that, without departing from the spirit and principles of the present invention, the technical solution can also be subjected to several simple modifications and substitutions, and these modifications and substitutions are also within the scope of protection covered by the claims.

Claims

1. A hydroxyethyl cellulose-aramid / MXene nano-friction positive electrode material, characterized in that: The positive electrode material has a sandwich structure, with an inner layer of an aramid / MXene vacuum-filtered composite film and an outer shell of a hydroxyethyl cellulose protective layer.

2. A method for preparing a hydroxyethyl cellulose-aramid / MXene nano-friction cathode material, characterized in that: The following steps are involved: Step 1, preparing a hydroxyethyl cellulose dispersion, an aramid nanofiber dispersion and a MXene dispersion; Step 2, after the aramid nanofiber dispersion and the MXene dispersion are evenly mixed, an ANF / MXene composite membrane is prepared by vacuum filtration and a first drying treatment; Step 3, immersing the ANF / MXene composite film in a hydroxyethyl cellulose dispersion, and then undergoing a second drying treatment to obtain an ANF / MXene-HEC triboelectric positive electrode material with a sandwich structure.

3. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 1, the preparation method of the hydroxyethyl cellulose dispersion is as follows: dissolving 3-4 g of hydroxyethyl cellulose powder in 100-150 mL of deionized water at 45-55° C. for 30-40 min to obtain a hydroxyethyl cellulose dispersion; wherein the viscosity of the hydroxyethyl cellulose is 2600-3300 mPa.s.

4. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 1, the aramid nanofiber mixed dispersion is prepared as follows: first, an alkaline solution, para-aramid fibers and dimethyl sulfoxide are stirred and mixed to obtain a dispersion A; wherein the mass ratio of the para-aramid fibers to the dimethyl sulfoxide is 2-3:200-300, the solute of the alkaline solution is potassium hydroxide, the concentration of the solute in the alkaline solution is 0.3-0.6 g / mL, and the ratio of the alkaline solution to the para-aramid fibers is 1-2 mL:2-3 g; Dispersion A is evenly dispersed in deionized water, and then filtered to obtain para-aramid nanofiber dispersion B; wherein the volume ratio of water to dispersion A is 1000-1500:50-100, and the concentration of the para-aramid nanofiber dispersion is 1%-1.5%.

5. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 1, the MXene aqueous dispersion is a nanosheet MXene aqueous dispersion prepared by an acid etching method, and the concentration of the MXene dispersion is 20 to 25 mg / mL.

6. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 2, the solution ratio of the aramid nanofiber dispersion and the MXene dispersion is 80-100 mL: 3-5 mL, and the mixture is stirred at 25-35° C. for 15-20 min to be uniformly mixed.

7. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 2, during vacuum filtration, the pressure is 0.08-0.10 MPa, the time is 3-4 hours, and the filtration membrane is a mixed fiber membrane or a polytetrafluoroethylene membrane; During the first drying process, the temperature is 95~105℃ and the drying time is 12~15min.

8. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 3, during the immersion, the concentration of the hydroxyethyl cellulose dispersion is 0.02 to 0.04 g / mL, and the immersion time is 3 to 5 minutes.

9. The method for preparing the hydroxyethyl cellulose-aramid / MXene nano-friction cathode material according to claim 2, characterized in that: In step 3, during the second drying process, the temperature is 60-70°C and the time is 6-8 hours.

10. A friction nano power generation device comprising the hydroxyethyl cellulose-aramid / MXene nano friction positive electrode material as claimed in claim 1.

Citation Information

Patent Citations

  • Modified nanocellulose / MXene flexible conductive composite film as well as preparation method and application thereof

    CN115490924A

  • Warm-keeping and moisturizing composite mask cloth based on larch fibers and preparation method of warm-keeping and moisturizing composite mask cloth

    CN116905220A

  • High-friction-voltage hydroxyethyl cellulose sensing material and preparation method thereof

    CN119116489A